Pharmacy Technician Workload and Workforce Requirements at MOH Primary Health Care Center during Ten years Mass Gathering Hajj (2006-2015) in Makah Region, Saudi Arabia - Alomi, Yousef Ahmed; Alhennawi, Khairat; Khayayt, Nizar (Journal of Pharmacy Practice and Community Medicine)
Purpose: To explore the pharmacy technician workload analysis and workforce requirements at Ministry of Health Primary health care centers during mass gathering Hajj ten years (2006-2015), Saudi Arabia. Methods: It is a retrospective of ten years (2006-2015) of primary health care center (PCC) pharmacy technician workload during mass gathering Hajj period. The duration of workload collection was 15 days. The pharmacy technician prepares medications and provide pharmaceutical for dispensing through the pharmacist all patients either Pilgrim or not Pilgrim at Makah region. It included Mona holy places hospitals; Arafat holy places hospitals, and Makah city. The workforce requirements calculated based on MOH workforce standards of primary health care center and the workload drives as central pharmacy technician services, patient specific pharmacy technician activities, and general administration specific pharmacy technician activities. Results: The total number of pilgrims (1,952,817-3,161,573) with average (2,445,208). The total number of prescriptions (226,824-505,753) with average (411,317), it represented (7.12-20.25%) with average (16.77%) of all pilgrims. The average number PCC prescription at holy places were (275,820) and (138,388.40) from Makah city. The average number of pharmacy technician needed (12.46FTE) per each PCC at holy places, and (13.99 FTE) per each PCC at Makah city with a total number of pharmacy technician was (26.45 FTE) per each PCC. The grand average number of pharmacist based on MOH standards for PCC was (1725.86 FTE) while the mean number pharmacy technician needed based on workload was (135.7 FTE) for all PCC. Conclusion: There is very high demand of pharmacy technician workforces during mass gathering Hajj time at primary health care center in Makka region. Targeting to change pharmacy technician workforces MOH standards requirements improve pharmacy technician services at primary care centers provided to all pilgrims in Makka region, Saudi Arabia.
Keywords: pharmacy technician; Workload; Workforces; Primary care center; Mass Gathering; Hajj; Makka; Ministry of Health; Saudi Arabia